Relationship between knowledge, attitude and action of adolescent girls with hygiene of external reproductive organs in the Oeolo health center working area - Nastiti, Deasy Harini (Journal Health of Indonesian, 2024)
Reproductive organs get less attention in everyday life, this is due to our culture that sometimes feels uncomfortable talking about sexual matters. In fact, these organs really need attention, especially their health and hygiene. This study aims to determine the knowledge, attitudes and actions towards the practice of maintaining the hygiene of reproductive organs of female students in the Oeolo Health Center working area. This type of research is descriptive research. The population of this study were all female students of the Oeolo Health Center working area, totaling 279 people, and a sample of 55 people was obtained. The results of this study showed that students with good knowledge were 47 people (85.5%), 8 people (14.5%) had sufficient knowledge. For a good attitude as many as 5 people (9.1%), 46 people (83.6%) and less attitude 4 people (7.3%). For good action 5 people (9.1%), sufficient action 19 people (34.5%) and less action 31 people (56.4%). The research suggestion is that in order to produce healthy offspring, it is also necessary to maintain the health of the reproductive organs. The school should include reproductive health education as an additional curriculum in the subject. The Education Office needs to provide training on how to maintain the hygiene and health of female reproductive organs facilitated by the local Health Office on reproductive health education to schools.